Dormancy, germination and emergence of Urochloa panicoides regulated by temperature - Ustarroz, Diego (2016)
Urochloa panicoides is an annual weed of summer crops. In Argentina, in subhumid areas with monsoon rainfall, it germinates and establishes in a single flush. To (i) identify the environmental factors that modify its seed dormancy level and germination and (ii) quantify the parameters describing the thermal behaviour of the germination and emergence dynamics of this weed under non‐limiting water conditions, we established a set of germination experiments performed (i) under controlled conditions using seeds after ripened for 3 or 6 months in different thermal and hydric conditions and (ii) under field conditions, where the soil temperature was modified by applying different shading levels. Seed dormancy level remained high with 3 months after ripening in all treatments. After 6 months, seeds stored at 4°C in dry conditions did not germinate at any temperature, while seeds stored at 25°C in dry conditions and in situ germinated c. 20% and 60% respectively. Germination percentage was higher in seeds harvested before their natural dispersal. The base, optimum and maximum temperatures for seed germination were 6, 35 and 45°C respectively. Shading reduced the number of emerged seedlings, possibly by reducing the soil thermal amplitude. The results explained the dormancy‐breaking mechanism of U. panicoides that allows a high germination rate in the field when rainfall occurs.